PENGARUH PERBEDAAN LABA AKUNTANSI DAN LABA FISKAL TERHADAP PERUBAHAN LABA - Riyana, Riyana; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of Book Tax Differences which are the permanent / fixeddifferences and the temporary / time differences to the profit changes on the mining companies which arelisted in Indonesia Stock Exchange in 2010-2014 periods. The hypotheses in this research i.e. (1) thepermanent differences have influence to the changes of accounting profit on the next periods. (2) Thetemporary differences have influence to the changes of accounting profit on the next periods.The samplesare 21 mining companies which are listed in Indonesia Stock Exchange (IDX) and these mining companieshave been selected by using purposive sampling from 2010 to 2014. From this data, 84 observations havebeen obtained as the research samples. The financial statement data has been obtained from Indonesia StockExchange STIESIA and www.idx.co.id. The quantitative method which has been carried out by using themultiple linear regressions as the analysis technique is applied as the research method.The result of theresearch shows that: (1) the permanent differences have negative influence to the changes of accountingprofit on the next periods. The permanent differences have negative influence since the items which exist inthe variables are re-added to the fiscal reconciliation. It has shown that the permanent / fixed differencesare the shaping component of book tax differences which influence the profit changes one period to thefuture. (2) The temporary differences have positive influence to the accounting profit on the next period. Thisvariable has positive influence because of the existence of the benefit of the deferred tax. It shows that thetemporary / time differences which are the shaping component of book tax differences has influence to theprofit changes on the next period.Keywords: Book Tax Differences, Permanent Differences, Temporary Differences, Profit Changes.